1999
DOI: 10.1088/0305-4470/32/24/306
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature expansion for Ising models on quasiperiodic tilings

Abstract: Abstract. We consider high-temperature expansions for the free energy of zerofield Ising models on planar quasiperiodic graphs. For the Penrose and the octagonal Ammann-Beenker tiling, we compute the expansion coefficients up to 18th order. As a by-product, we obtain exact vertex-averaged numbers of self-avoiding polygons on these quasiperiodic graphs. In addition, we analyze periodic approximants by computing the partition function via the Kac-Ward determinant. For the critical properties, we find complete ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…A discussion of the methods of generation and geometrical properties of this tiling can be found in [13], here we only mention a particularly useful feature, namely that embedding numbers of finite patches from this tiling can be calculated exactly and take the form n + mτ where τ = ( √ 2 + 1)/2 is the golden number and n, m are rational numbers. The calculation of the series expansion consists therefore of the following steps:…”
Section: Calculation Of Series Expansion For the Penrose Tilingmentioning
confidence: 99%
See 3 more Smart Citations
“…A discussion of the methods of generation and geometrical properties of this tiling can be found in [13], here we only mention a particularly useful feature, namely that embedding numbers of finite patches from this tiling can be calculated exactly and take the form n + mτ where τ = ( √ 2 + 1)/2 is the golden number and n, m are rational numbers. The calculation of the series expansion consists therefore of the following steps:…”
Section: Calculation Of Series Expansion For the Penrose Tilingmentioning
confidence: 99%
“…Moreover, as opposed to the square lattice graphs in the PT can have different "boundary line fillings", i.e. there are different graphs having the same boundary line [13]. Knowing that the PT contains eight different vertex types, i.e.…”
Section: Calculation Of Series Expansion For the Penrose Tilingmentioning
confidence: 99%
See 2 more Smart Citations
“…Finite approximants to the aperiodic Penrose tiling have been constructed through periodic pentagrids or projection methods. (78,79,80,73) The mathematician Robinson has brought to our attention an exercise in the book by Grünbaum and Shephard (81) where a tiling with Penrose rhombuses can be cut into patches, and then converted into an aperiodic set of 24 Wang's tiles. We have found that each patch in the Penrose tiling described in the exercise is in fact the image of a parallelogram under the mapping (2.5).…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%